THE PRAGMATIC ANALYSIS OF PRESENTATION OF EMOTIONS IN THE ENGLISH AND UZBEK LANGUAGES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article presents a pragmatic analysis of how emotions are presented and expressed in the English and Uzbek languages. Using a comparative approach, the study examines how emotions are conveyed through linguistic and non-linguistic means in both languages, and how cultural factors influence the expression and interpretation of emotions. The study also explores the role of context, speaker intention, and audience expectations in shaping the presentation of emotions in different communicative contexts. Data for the analysis were collected through observation of naturalistic conversations, interviews, and written texts in both languages. The findings suggest that while there are similarities in the way emotions are expressed in both languages, there are also significant differences related to cultural norms, values, and expectations. The study has implications for language teaching and intercultural communication, as it highlights the importance of understanding cultural and pragmatic factors in the presentation and interpretation of emotions in different linguistic and cultural contexts.